2013
DOI: 10.14712/18059694.2014.24
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Aspergillosis in Intensive Care Unit Patients in Iran

Abstract: Summary:We assessed the intensive care unit (ICU) patients for Invasive aspergillosis (IA) with culture and non-culture based diagnostic methods from Iran. Thirty-six ICU patients with underlying predisposing conditions for IA were enrolled in the study. Sixty eight Bronchoalveolar lavage (BAL) samples were collected by bronchoscope twice a weekly. BAL samples were analyzed by microscopic examination, fungal culture and galactomannan (GM) detection. The Platelia Aspergillus GM EIA was used to quantify GM indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In previous studies (7,(12)(13)(14), using a cut-off index of ≥ 1, the sensitivity and specificity values of GM detection in BAL fluid were 85% to 100% (14,15). Therefore, GMI 1.0 or greater in 2 consecutive samples was considered as positive in this study.…”
Section: Resultsmentioning
confidence: 91%
“…In previous studies (7,(12)(13)(14), using a cut-off index of ≥ 1, the sensitivity and specificity values of GM detection in BAL fluid were 85% to 100% (14,15). Therefore, GMI 1.0 or greater in 2 consecutive samples was considered as positive in this study.…”
Section: Resultsmentioning
confidence: 91%
“…A. fumigatus is globally found in the hospital environments and most frequently isolated from patients with IA or aspergilloma [ 28 - 34 ]. the highest airborne Aspergillus conidia concentrations due to the construction inside or surroundings area of the hospitals as well as problems in the ventilation or conditioner systems have proposed the environment to be the potential source of infection [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Hedayati et al in Iran, out of 36 suspected patients to IA, 36.1% of cases showed IA which were categorized as 4 cases of possible IA and 9 of probable IA. 35 In the present study we applied GM detection in BAL. Some authors suggested that it can be beneficial to detect GM in BAL fluid for IA diagnosis.…”
Section: Discussionmentioning
confidence: 99%